Kajian Filosofis Tentang Keadilan Sosial Dari Pemikiran Plato - Dules Ery Pratama Hrp; Yakobus Ndona (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Philosophical study of social justice from Plato's thought Throughout the history of philosophy, the topic of justice has been a very important topic. Theoretical thinkers such as utilitarianism, intuitionism, eudaimonism, perfectionism, liberalism, communitarianism, and socialism have discussed this topic. The core of political research from the time of Plato to the present is justice. Questions of fairness cannot be determined by the standards used to determine whether something is fair. Different versions of answers regarding the meaning of justice are often considered unsatisfactory, so they cannot be separated from the debate which ultimately constructs the meaning of justice itself, even into a relative formulation. This problem ultimately encouraged many groups to take an alternative path by returning the meaning of justice to those who set the laws and regulations and to judges who will develop their own considerations. This article will discuss the concept of justice from the perspective of Pre-Christian philosophers, especially Plato. Philosophically, there are two ways of expressing justice: First, the view that justice means harmony between the implementation of rights and the implementation of obligations according to the "balance of law" clause, namely "the scope of rights and obligations". The view of legal experts basically holds that justice is harmony between legal certainty and legal comparability. There are even those who argue that law must be combined with justice for it to truly have legal meaning. This is related to the answer that law is part of human efforts to create ethical coexistence in the world. Only through a just legal system can society live peacefully towards happiness, because the essence of law is to create fair rules in society.